Effect of aqueous extract from turmeric (Curcuma longa) on Xanthomonas axonopodis pv. manihotis - Kuhn, Odair José; Portz, Roberto Luiz; Stangarlin, José Renato; Del Águila, Ricardo Montalván; Schwan-Estrada, Kátia Regina Freitas; Franzener, Gilmar (Semina: Ciências Agrárias, 2006)
The control of Xanthomonas axonopodis pv. manihotis was evaluated in vitro by using aqueous extract of four turmeric genotypes from Jaboticabal-SP, Mara Rosa-GO, Maringá-PR and Mercedes-PR, as well as in vivo, by treatment of infected cassava stems and their cultivation at field conditions. The results showed that in vitro experiment, turmeric extract inhibited completely the bacteria growth in the concentration of 10% for the genotype from Mercedes, while for the Jaboticabal's turmeric there was a total control at 15% and for Mara Rosa at 20%. Turmeric genotype from Maringá did not show full inhibition of the bacterial growth in none of the extract concentrations used. At field conditions, sproutings were extremely low, due to the stems infection degree. Turmeric extract at 10%, from Mercedes, was harmful for the cassava, reducing stand regarding the control treatments. Possibly there was a direct toxic action on the plant physiology or susceptibility induction. But in the concentration of 1% of turmeric from Maringá, there was no statistical difference in relation to the control treatment for the plant stand. The chemical control was not completely efficient. There was no statistical difference among treatments for both severity and productivity. The results indicate that, although presenting antibacterial activity to X. axonopodis pv. manihotis, the turmeric extracts, in the used concentrations, did not present curative effect in cassava stems infected with the pathogen.